Relationship Between Islamic Teachings (Haram of The Pork Consumption) and Human Health (Biology) - Khilma Novia Amalina (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
Each religion has its own teaching or rules including Islam. Islam is revealed by Allah SWT to spread goodness and salvation or so called Rahmatanlill'alamiin (blessing to the entire universe), so that the teachings won’t harm the believer, one of the teachings of Islam is the haram to consume pork. The prohibition has no such clear reason in Al-Qur'an. The reason can only be clarified by using science method that is appropriate to the problem. One of the science that can clarify the reason is biology. In this paper the authors will correlate the teachings of Islam (haram of the pork consumption) and human health (biology). The method used is the analysis of the results research and literature study. It can be seen that the teachings of Islam haram of the pork consumption, because pork contains parasites.